Pengaruh Government Size, Fiscal Distress, dan Sisa Lebih Perhitungan Anggaran Terhadap Manipulasi Akrual - Lisda Tampubolon; Evada Dewata; Desi Indriasari; Hadi Jauhari (Jurnal Akuntansi Bisnis, 2023)
This study aims to examine the factors that influence accrual manipulation, namely Government size, Fiscal Distress, and SiLPA using the Modified Jones model. The data used is secondary data in the form of Regional Government Financial Statements of 17 districts/cities in South Sumatra Province for the five-year period 2017-2021. Using the EVIEWS version 12 program as a multiple regression tool. The research findings obtained are that Government Size does not have a significant effect on accrual manipulation while Fiscal distress and SiLPA have a significant effect on accrual manipulation. The implications of these findings can be used as a basis for the development of better accounting policies and practices that focus on ongoing fiscal policy oversight and improved integrity in local government financial reporting.